Wind power forecast using neural networks: Tuning with optimization techniques and error analysis - Nazaré, Gonçalo; Castro, Rui; Gabriel Filho, Luís R.A. [UNESP] (Wiley, 2020)
The increased integration of wind power into the power system implies many challenges to the network operators, mainly due to the hard to predict and variability of wind power generation. Thus, an accurate wind power forecast is imperative for systems operators, aiming at an efficient and economical wind power operation and integration into the power system. This work addresses the issue of forecasting short-term wind speed and wind power for 1 hour ahead, combining artificial neural networks (ANNs) with optimization techniques on real historical wind speed and wind power data. Levenberg-Marquardt (LM) and particle swarm optimization (PSO) are used as training algorithms to update the weights and bias of the ANN applied to wind speed predictions. The forecasting performance produced by the proposed models are compared with each other, as well as with the benchmark persistence model. Test results show higher performance for ANN-LM wind speed forecasting model, outperforming both ANN-PSO and persistence. The application of ANN-LM to wind power forecast revealed also a good performance, with an average improvement of 2.8% in relation to persistence. An innovative analysis of mean absolute percentage error (MAPE) behaviour in time and in typical days is finally offered in the paper.
Keywords: artificial neural network; Levenberg-Marquardt; particle swarm optimization; short-term wind forecast